(untitled) (SCIENCE TIME JOURNAL, 2025)
This article investigates the integration of 4K competencies—critical thinking, communication, collaboration, and creativity—within music education to enhance student learning outcomes, addressing the pressing issue of inadequate pedagogical strategies for effectively fostering these skills. Utilizing a mixed-methods approach, the research includes qualitative data from classroom observations and teacher interviews, alongside quantitative assessments of student performance. The findings reveal that structured approaches to implementing 4K competencies significantly improve students engagement and skill acquisition in music lessons, leading to higher performance levels and enhanced collaborative experiences. These results underscore the importance of integrating innovative pedagogical frameworks into music education, suggesting that well-developed 4K competencies not only facilitate better learning outcomes in music but also promote essential skills applicable in healthcare settings. The implications of this study extend beyond music education, highlighting the potential for interdisciplinary applications that can foster a more holistic approach to education in various fields, including healthcare. By equipping students with these competencies, educators can prepare them for future challenges in a rapidly evolving landscape, ultimately contributing to the development of more effective healthcare professionals who are adept at critical thinking, teamwork, and creative problem-solving.